2018
DOI: 10.1016/j.revpalbo.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Modern pollen–vegetation relationships in traditionally mown and unmanaged boreal rich-fen communities in central Norway

Abstract: Knowledge of the relationship between vegetation and modern pollen deposition is necessary to improve the interpretation of fossil pollen samples. We compared the cover of plant species and the modern pollen deposition in surface moss samples in 49 plots in rich-fen vegetation from the boreal vegetation zone in Norway in two areas (one oceanic and one more continental). These rich fens were used for traditional hay cutting until ca. 1950. Three management regimes are used: 1) biennial mowing 2) quadrennial mow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
2
4
0
1
Order By: Relevance
“…In forested sites, Cyperaceae produce less pollen and the pollen signal is overwhelmed by tree pollen (Waller et al., 2005). Succisa ( Succisa pratensis ), which was an indicator of forested fens in our study, has been shown to be associated with unmanaged (not mown) fens in Norway (Fjordheim et al., 2018). Polypodiaceae and Prunus have also been shown to be associated with forested fen vegetation in English fens (Waller et al., 2017) and Polypodiaceae has been associated with increasing abundance of Pinus pollen in Latvian mire reconstructions (Ozola, 2013).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In forested sites, Cyperaceae produce less pollen and the pollen signal is overwhelmed by tree pollen (Waller et al., 2005). Succisa ( Succisa pratensis ), which was an indicator of forested fens in our study, has been shown to be associated with unmanaged (not mown) fens in Norway (Fjordheim et al., 2018). Polypodiaceae and Prunus have also been shown to be associated with forested fen vegetation in English fens (Waller et al., 2017) and Polypodiaceae has been associated with increasing abundance of Pinus pollen in Latvian mire reconstructions (Ozola, 2013).…”
Section: Discussionsupporting
confidence: 53%
“…Succisa (Succisa pratensis), which was an indicator of forested fens in our study, has been shown to be associated with unmanaged (not mown) fens in Norway (Fjordheim et al, 2018). Polypodiaceae and…”
Section: The Modern Pollen Signal In Different Mire Typesmentioning
confidence: 50%
See 1 more Smart Citation
“…However, some promising technical innovation such as confocal microscopy might help in the future (Seppä and Bennett 2003). Interestingly, Eriophorum and Carex pollen (both apophytic Cyperaceae) could be amalgamated into Dulichium-type (Faegri and Iversen 1975), which might allow tentative reconstructions of landuse regimes (Fjordheim et al 2018) in the absence of other more specific human indicators. Dissimilarities derived from taxonomic precision were very high (up to 10%) during the Modern Period (after ad 1600; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…donde B 0 es el número de transectos donde están presentes tanto el tipo polínico como el grupo vegetal asociado; P 0 representa el número de transectos donde se registra el polen, pero la planta que lo produce no está presente en la vegetación, y P 1 es el número de transectos donde el tipo de polen está ausente, pero el taxón vegetal está presente en la vegetación. Según Fjordheim et al (2018), los valores de los índices de cada taxón se agruparon en las siguientes categorias: 1) tipo fuertemente asociado "TFA" cuando A > 0.65; 2) tipo asociado "TA", cuando A varía entre 0.65 y 0.5; 3) tipo débilmente asociado "TDA", donde A < 0.5 y además O y U son positivos; 4) tipo sobrerrepresentado "TOR", cuando A < 0.5 y U = 0; 5) tipo subrepresentado "TUR", con A < 0.5 y O = 0, y 6) tipo no asociado "TNA", en donde A = 0, además O y U son positivos. https://doi.org/10.…”
Section: Materiales Y Métodosunclassified